ผลของโปรแกรมพัฒนาทักษะการเผชิญความเครียดในการป้องกันการเสพซ้ำต่อการรับรู้ความสามารถแห่งตนในการเลิกใช้สารแอมเฟตามีนของผู้เสพติดสารแอมเฟตามีน - กฤษดา ทองทับ (จุฬาลงกรณ์มหาวิทยาลัย, 2012)
The purpose of this quasi-experimental research using pretest-posttest randomized control group design were to compare: 1) the abstinence self-efficacy of amphetamine before and after received coping skills training in relapse prevention program, and 2) the abstinence self-efficacy of amphetamine between amphetamine users in the experimental group who received coping skills training in relapse prevention program and those in the control group who received regular nursing care. A total sample of 40 amphetamine dependence patients who met the inclusion criteria were purposively recruited from out-patient department, Sena Hospital. The samples were matched-pair according to age, educational level and age at start using amphetamine, and then randomly assigned into experimental group and control group, 20 subjects in each group. The research instruments consisted of 1) the Coping Skills Training in Relapse Prevention Program, 2) the Abstinence Self-efficacy Scale and 3) the Relapse Coping Questionnaire. All instruments were verified for content validity by 5 professional experts. Chronbach’s alpha coefficient reliability of the 2nd and 3rd instrument was .81 and .84 respectively. The t-test was used in data analysis. Major findings were as follow: 1) The abstinence self-efficacy of amphetamine dependence after participating in program was significantly higher than that before ( =106.45 and 138.50 respectively, t =-11.742, p< .05). 2) The abstinence self-efficacy of amphetamine dependence after participated in program was higher than those who participated in the regular nursing care ( =138.50 and 113.25 respectively, t = 7.104, p< .05).